IMPLEMENTASI MANAJEMEN KURIKULUM DALAM MENINGKATKAN MUTU PEMBELAJARAN DI MA MA’HAD MANAHILIL ULUM GUPPI SAMATA - S, M. Fadil; Niswa, Niswa; Mulia, St. Nurfaedah; Amiruddin, Idris (Department of Islamic Education Management, 2026)
This study aims to describe the implementation of curriculum management in improving the quality of learning at MA Ma'had Manahilil Ulum GUPPI Samata, Gowa. The research employed a descriptive qualitative approach, with data collected through interviews, observation, and documentation, analyzed through data reduction, data display, and conclusion drawing, and validated through source and technique triangulation. The results show that curriculum planning was carried out through the development of learning outcome flows (ATP) and teaching modules, supported by workshops and training. Curriculum implementation was strengthened by ongoing coordination between school leadership and teachers to avoid content overlap in the implementation of the Merdeka Curriculum. Teacher development was carried out through mentoring and academic supervision, while curriculum evaluation included the examination of learning tools, classroom monitoring, and follow-up improvements. Student learning outcomes were evaluated through both formative and summative assessment, serving as the basis for remedial and enrichment programs. The main challenges included the initial adaptation to the Merdeka Curriculum and variation in teacher readiness; nevertheless, curriculum management implementation was shown to support more focused learning and sustained quality improvement. These findings can serve as a practical reference for madrasah principals and teachers in strengthening curriculum planning, coordination, and evaluation, while also enriching the academic literature on curriculum management in Islamic-based madrasah, particularly within the context of the Merdeka Curriculum.